Protein expression changes during human triple negative breast cancer cell line progression to lymph node metastasis in a xenografted model in nude mice - Roberti, Maria Paula (2012)
Triple negative breast cancers (TNBC) lacking hormone receptors and R-2 amplification are very aggressive tumors. Since relevant differences between primary tumors and metastases could arise during tumor progression as evidenced by phenotypic discordances reported for hormonal receptors or R-2 expression, in this analysis we studied changes that occurred in our TNBC model IIB-BR-G throughout the development of IIB-BR-G-MTS6 metastasis to the lymph nodes (LN) in nude mice, using an antibody-based protein array to characterize their expression profile. We also analyzed their growth kinetics, migration, invasiveness and cytoskeleton structure in vitro and in vivo. In vitro IIB-BR-G-MTS6 cells grew slower but showed higher anchorage independent growth. In vivo IIB-BR-G-MTS6 tumors grew significantly faster and showed a 100% incidence of LN metastasis after s.c. inoculation, although no metastasis was observed for IIB-BR-G. CCL3, IL1β, CXCL1, CSF2, CSF3, IGFB1, IL1α, IL6, IL8, CCL20, LUR, lGF and VGF were strongly upregulated in IIB-BR-G-MTS6 while CCL4, ICM3, CXCL12, TNFRSF18, FIGF were the most downregulated proteins in the metastatic cell line. IIB-BR-G-MTS6 protein expression profile could reflect a higher NFκB activation in these cells. In vitro, IIB-BR-G displayed higher migration but IIB-BR-G-MTS6 had more elevated matrigel invasion ability. In agreement with that observation, IIB-BR-G-MTS6 had an upregulated expression of MM1, MM9, MM13, LUR and GF. IIB-BR-G-MTS6 tumors presented also higher local lymphatic invasion than IIB-BR-G but similar lymphatic vessel densities. VGFC and VGF/B expression were higher both in vitro and in vivo for IIB-BR-G-MTS6. IIB-BR-G-MTS6 expressed more vimentin than IB-BR-G cells, which was mainly localized in the cellular extremities and both cell lines are -cadherin negative. Our results suggest that IIB-BR-G-MTS6 cells have acquired a pronounced epithelial-to-mesenchymal transition phenotype. rotein expression changes observed between primary tumor-derived IIB-BR-G and metastatic IIB-BR-G-MTS6 TNBC cells suggest potential targets involved in the control of metastasis.